Розкопки на трипільському поселенні у с. Чаплинка - Овчинников, Е.В. (Археологічні дослідження в Україні, 2010)
In 2008 and 2009, permanent excavations at Trypillya settlement Chaplynka in Burty tract in Lysyanka Region of Cherkasy Oblast were conducted for the first time. Several husbandry objects and a ground-based structure-«platform» were studied. The platform included two tiers: the upper formed with wooden and cob «platform», and the lower presented with three cob pavements on the floor made of soil. The finds include: whole cups, fragments of ceramic and sculptures, and tools. The site is referred to Volodymyrivka and Tomashivka group (the 2nd Nebelivka phase) with profound influences of Kaniv group of Western Trypillya culture.